Optimization of Phase Space files from clinical linear accelerators. (August 2019) - Martins, Juliana Cristina; Saxena, Rangoli; Neppl, Sebastian; Alhazmi, Abdulaziz; Reiner, Michael; Veloza, Stella; Belka, Claus; Parodi, Katia
Highlights: A general methodology for optimization of existing Phase Space files was developed. A linear relationship between beam divergence and lateral profiles was obtained. Optimization factors for particles' energy and direction have been identified. Remarkable improvement in the agreement among measured and simulated data observed. Viable alternative in absence of geometric information and validated Phase Space. Abstract: This work proposes a methodology to produce an optimized phase-space (PhSp) for the Elekta Synergy linac by tuning the energy and direction of particles inside the 6-MV Elekta Precise PhSp, provided by the International Atomic Energy Agency (IAEA), for Monte Carlo (MC) simulations. First, the energies of the particles emerging from the original PhSp were increased by different factors, producing new PhSps. Percentage depth dose (PDD) profiles were simulated and compared to measured data from a Synergy linac for 6-MV photon beam. This process was repeated until a minimum difference was reached. Particles' directions were then manipulated following identified correlations to lateral profiles, resulting in two distinct perturbation factors based on inline and crossline profiles. Both factors were merged into one single optimal factor. For energy optimization, an increase of 0.32 MeV applied to all particles inside the original PhSp, but to 0.511 MeV annihilation photons, provided the best results. The direction optimization factor was the combination of the individual factors for inline (0.605%) and crossline (0.051%). The agreement between measured and simulated profiles, when using the optimized PhSp, improved considerably in comparison to simulations performed with the original IAEA PhSp. For all fields and depths analyzed, the discrepancies for PDD, inline and crossline profiles dropped from 11.2%, 15.7% and 27.5% to under 1.4%, 4.7% and 13.2%, respectively. The optimized PhSp should not replace the full linac modelling, however it offers an alternative for MC dose calculations when neither geometric details nor validated IAEA PhSp are available to the user.